2011
DOI: 10.1080/03067319.2010.496048
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of polychlorinated biphenyls in fish by pressurised liquid extraction with in-cell cleanup and GC-MS

Abstract: An improved, rapid method for polychlorobiphenyl (PCB) extraction from lipid rich matrices and determination by GC-MS is presented. PCBs accumulate in the environment, can be extremely persistent, and health complications including neurotoxic effects have been reported. Thus, monitoring these persistent organic pollutants seems prudent. The analytical procedure for PCB assessment from environmental samples typically consists of the three steps extraction, purification and analysis by GC coupled with electron-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…PLE is becoming more popular because it can be highly automated and unattended extractions can be performed overnight to improve sample throughput. In addition to that, many authors [9,10,25,26,28,33,42,47,48] attempted in-cell clean-up by packing different absorbents and copper with samples inside the cell for simultaneous extraction and clean-up with good analyte recovery and precision.…”
Section: Sample Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…PLE is becoming more popular because it can be highly automated and unattended extractions can be performed overnight to improve sample throughput. In addition to that, many authors [9,10,25,26,28,33,42,47,48] attempted in-cell clean-up by packing different absorbents and copper with samples inside the cell for simultaneous extraction and clean-up with good analyte recovery and precision.…”
Section: Sample Extractionmentioning
confidence: 99%
“…So far, routine procedures {e.g., sulfuric-acid treatment [15,21] and gel-permeation chromatography [10]}, and multi-column separation using acidified and/ or alkalinized silica, alumina, and Florisil, silver-nitrateimpregnated silica absorbents [8,[12][13][14][15][16][20][21][22][23]60] are being widely adopted and becoming absolutely necessary. Some authors [9,11,25,26,28,33,42,47] combined extraction and clean-up in one run and substantially reduced the solvent used and time required for sample preparation.…”
Section: Clean-upmentioning
confidence: 99%
“…Shaogang et al [25] reported a total PCB level of 0.864µg/g for fish samples analyzed in China which was found to be higher than the concentration obtained in this study. Also, a total PCB concentration of 0.094 µg/g for fish sample (trout) caught in Luxembourg was reported by Cocco et al [26].…”
Section: Discussionmentioning
confidence: 77%
“…The final extract of the sample was evaporated to dryness under a stream of nitrogen, reconstituted by the addition of 0·5 ml hexane and then transferred to two vials with a 250 μl insert for determination by GC–MS/MS. The detection by GC–MS/MS was performed in a gas chromatograph coupled to a triple-quadrupole mass detector (TSQ Quantum™, ThermoFisher Scientific) equipped with a DB-XLB column (30 m length, 0·250 mm diameter, 0·50 μm film thickness) ( 24 , 25 ) .…”
Section: Methodsmentioning
confidence: 99%